Design Of Decision Support System Final Project Topic In Computer And Network Engineering Study Program State Polytechnic Of Ujung Pandang - Tamrin, Fadli; Olivya, Meylanie; Azzahra, Maryam (Jurnal Teknologi Elekterika, 2025)
This research is motivated by the difficulties often experienced by students in determining the topic of their final assignment that suits their interests and abilities, which results in delayed graduation. The purpose of this study is to create an accurate final assignment topic decision support system model using the Random Forest Algorithm, design a website-based decision support system to assist students in determining the topic of their final assignment, and evaluate the efficiency and quality of the system. The data used are academic grades and interests of students in the Computer and Network Engineering study program at the Ujung Pandang State Polytechnic. The results of the study show that the Random Forest Model is able to produce final assignment topic recommendations with a Cross-validation accuracy of 61.36%. The website-based decision support system designed can assist students in determining the topic of their final assignment according to their interests and academic abilities, as well as improve the efficiency and quality of the final assignment topic selection process. This research contributes to making it easier for students to find the right final assignment topic, as well as providing guidance for the development of similar recommendation systems in the future.